2019
DOI: 10.1093/gji/ggz037
|View full text |Cite
|
Sign up to set email alerts
|

Precessing spherical shells: flows, dissipation, dynamo and the lunar core

Abstract: Precession of planets or moons affects internal liquid layers by driving flows, instabilities and possibly dynamos. The energy dissipated by these phenomena can influence orbital parameters such as the planet's spin rate. However, there is no systematic study of these flows in the spherical shell geometry relevant for planets, and the lack of scaling law prevents convincing extrapolation to celestial bodies.We have run more than 900 simulations of fluid spherical shells affected by precession, to systematicall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 66 publications
1
77
0
Order By: Relevance
“…Because of the sharp spatial attenuation of this field outside the core, the larger length scale part would dominate the field recorded at the lunar surface, but it may only amount to a fraction of a μT. Indeed, numerical models of dynamos generated by precession at the CMB suggest this is the case (Cébron et al, 2019). Hence, a lunar dynamo from precession at the ICB generating surface field strengths of a fraction of a μT may be compatible with the weak paleointensities recorded after 1 Ga, which would push the end of the lunar dynamo to more recently than 0.44 Ga. We hope that our results may serve as a motivation to modelers to attempt to address these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the sharp spatial attenuation of this field outside the core, the larger length scale part would dominate the field recorded at the lunar surface, but it may only amount to a fraction of a μT. Indeed, numerical models of dynamos generated by precession at the CMB suggest this is the case (Cébron et al, 2019). Hence, a lunar dynamo from precession at the ICB generating surface field strengths of a fraction of a μT may be compatible with the weak paleointensities recorded after 1 Ga, which would push the end of the lunar dynamo to more recently than 0.44 Ga. We hope that our results may serve as a motivation to modelers to attempt to address these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Du et al (2017) and Badro et al (2018) found exsolution of MgO in Earth's core to be possible, but it does not produce sufficient heat to replace radiogenic decay in the thermal budget of the core (Du et al, 2017), which is needed to resolve both the cooling of the mantle and the driving of the core dynamo (Driscoll & Bercovici, 2014). Tidal forcing could potentially drive core flows but they are predicted to prefer thermally stratified regions (Cebron et al, 2010); so it remains unclear whether they can power a dynamo (e.g., Cébron et al, 2019).…”
Section: Application To Earth's Corementioning
confidence: 99%
“…Similar concentrated wave beams are also found in rotating fluids (Kerswell, 1995;Le Dizès & Le Bars, 2017). They have mainly been studied in spherical geometries (Calkins et al, 2010;Koch et al, 2013;Cébron et al, 2019;Lin & Noir, 2020) in the context of planetary applications (Le Bars et al, 2015). These wave beams are the temporal equivalent of the thin shear layers found at the periphery of Taylor-Proudman columns between differentially rotating disks or spheres (Proudman, 1956;Stewartson, 1966).…”
Section: Introductionmentioning
confidence: 74%